Monitoring and Evaluasi of Poultry Slaughter at Traditional Market - Sitti Zubaidah; Suryani (Universitas Djuanda, 2024)
The low level of halal certification at locations selling poultry products in Bireuen District will have an impact on reducing the purchasing and consumption of poultry products by consumers in the future. The Halal Product Guarantee Organizing Agency by the Ministry of Religion of the Republic of Indonesia has advised that every business actor must have a Halal Certificate by 2024, and this will have an impact on poultry farming business actors in Bireuen Regency. The aim of this research is that to monitoring and evaluating the poultry slaughter in the traditional markets of Bireuen District. The research method used was a survey method through observation, questionnaires and interviews. The research results obtained were the characteristics of poultry slaughterers aged between 17-30 years (59.38%) with high school education (75%), length of business under 5 years (67.19) with ownership status belonging to someone else (90.63 %), the number of poultry slaughtered is between 50-100 heads every day (68.75%) and do not have a Halal Slaughter Certificate (JULEHA) (92.19%). In conclusion, it is necessary to provide socialization and training on halal slaughter of poultry products to poultry slaughterers by Local Government at the Bireuen Regency Traditional Market.